2015
DOI: 10.2119/molmed.2014.00240
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatic Insulin Resistance Contributes to Hyperglycemia in Rats Following Myocardial Infarction

Abstract: Although hyperglycemia is common in patients with acute myocardial infarction (MI), the underlying mechanisms are largely unknown. Insulin signaling plays a key role in the regulation of glucose homeostasis. In this study, we test the hypothesis that rapid alteration of insulin signaling pathways could be a potential contributor to acute hyperglycemia after MI. Male rats were used to produce MI by ligation of the left anterior descending coronary artery. Plasma glucose and insulin levels were significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The mechanisms for IR and IGT to develop as a result of MI have not been fully established. It has been suggested that the post-MI catecholamine stress induces hyperglycemic, inflammatory and lipolytic response, progressively affecting metabolism in peripheral tissues, and may lead to the development of IR, IGT, and type 2 diabetes, especially in obese subjects [ 11 , 13 , 53 – 55 ]. BAT activation consumes substantial amounts of glucose as fuel for thermogenesis, contributing significantly to whole-body glucose disposal [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for IR and IGT to develop as a result of MI have not been fully established. It has been suggested that the post-MI catecholamine stress induces hyperglycemic, inflammatory and lipolytic response, progressively affecting metabolism in peripheral tissues, and may lead to the development of IR, IGT, and type 2 diabetes, especially in obese subjects [ 11 , 13 , 53 – 55 ]. BAT activation consumes substantial amounts of glucose as fuel for thermogenesis, contributing significantly to whole-body glucose disposal [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the complicated characteristics in biological mechanisms, the interaction between hyperglycemia and myocardial I/R injury further increases the complex to investigate the mechanisms. Indeed, we found myocardial ischemia per se caused hyperglycemia through hepatic insulin signaling blunting [ 27 ], besides that hyperglycemia resulted in exacerbation of myocardial I/R injury [ 2 , 3 , 28 ], which formed a vicious cycle leading to poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced in body weight could be attributed to the reduction of hyperinsulinemia and improvement of IR and leptin sensitivity. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%